L, P-/Q- and T-type Ca channels in smooth muscle cells from human umbilical artery - Salemme, Silvia Verónica (2007)
The electrophysiological and pharmacological properties of Ca 2+ current (I Ca ) were determined by the whole-cell configuration of the patch-clamp technique in smooth muscle cells from human umbilical artery. Using 5 mM extracellular Ca 2+ , depolarizing step pulses from -60 to 50 mV from a holding membrane potential of -80 mV evoked an I Ca which activated at membrane potentials more positive than -50 mV and exhibited a maximum current density in a range of 10-20 mV. Steady-state inactivation protocols using a V test of 10 mV gave a voltage at one-half inactivation and a slope factor of -35.6 mV and 9.5 mV, respectively. Nifedipine (1 μM), an L-type Ca 2+ channels antagonist, completely inhibited I Ca , while the L-type Ca 2+ channels agonist Bay-K 8644 (1 μM) significantly increased I Ca amplitude. Moreover, the selective blocker of P-/Q-type Ca 2+ channels ω-agatoxin IVA partially blocked I Ca (about 40 % inhibition at +20 mV by 20 nM). These pharmacological results suggest that L- and P-/Q-type Ca 2+ channels, both nifedipine-sensitive, underlie the I Ca registered using low extracellular Ca 2+ . The presence of the P-/Q-type Ca 2+ channels was confirmed by immunoblot analysis. When I Ca was recorded in a high concentration (30 mM) of extracellular Ca 2+ or Ba 2+ as current carrier, it was evident the presence of a nifedipine-insensitive component which completely inactivated during the course of the voltage-step (75 ms) at all potentials tested, and was blocked by the T-type Ca 2+ channels blocker mibefradil (10 μM). Summarizing, this work shows for the first time the electrophysiological and pharmacological properties of voltage-activated Ca 2+ currents in human umbilical artery smooth muscle cells.